2009
DOI: 10.1155/2009/976401
|View full text |Cite
|
Sign up to set email alerts
|

Endourologic Management of Upper Tract Transitional Cell Carcinoma following Cystectomy and Urinary Diversion

Abstract: Traditionally, nephroureterectomy is the gold standard therapy for upper tract recurrence of transitional cell carcinoma (TCC) following cystectomy and urinary diversion. With advances in endoscopic equipment and improvements in technique, conservative endourologic management via a retrograde or antegrade approach is technically feasible with acceptable outcomes in patients with bilateral disease, solitary renal units, chronic renal insufficiency, or significant medical comorbidities. Contemporary studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Conservative endoscopic management via retrograde or percutaneous antegrade approaches as well as nephron-sparing surgery are now feasible alternatives, even in patients with normal contralateral kidneys. 22 Accurate staging by combining cross-sectional imaging techniques and endoscopic evaluation with biopsy is key to selecting the most appropriate treatment option. 7 According to the European Association of Urology (EAU) guidelines on UTUC, the indications for endourological management include unifocal low-grade tumour, which is less than 1 cm with no evidence of infiltration on CTU.…”
Section: Disease Managementmentioning
confidence: 99%
“…Conservative endoscopic management via retrograde or percutaneous antegrade approaches as well as nephron-sparing surgery are now feasible alternatives, even in patients with normal contralateral kidneys. 22 Accurate staging by combining cross-sectional imaging techniques and endoscopic evaluation with biopsy is key to selecting the most appropriate treatment option. 7 According to the European Association of Urology (EAU) guidelines on UTUC, the indications for endourological management include unifocal low-grade tumour, which is less than 1 cm with no evidence of infiltration on CTU.…”
Section: Disease Managementmentioning
confidence: 99%
“…[ 12 ] A further indication of antegrade treatment is in patients with previous urinary diversion, most commonly prior cystectomy for bladder TCC, though retrograde access may be possible but often technically challenging. [ 14 15 ] A combined retrograde and antegrade approach may be necessary in patients with multifocal upper tract TCC or a renal pelvic tumor with superficial extension down the ureter. [ 16 ]…”
Section: Endoscopic Managementmentioning
confidence: 99%
“…Furthermore, retrospective series have suggested that metastasis-directed treatment (MDT) could improve cancer-specific and overall survival with a low toxicity profile [14,15]. In particular, stereotactic body radiotherapy (SBRT) has been described as safe and feasible, allowing the postponement of systemic treatment [16][17][18][19]. Moreover, Steuber et al, reported that combination of SBRT and ADT in OPC patients might improve local control and might decrease the risk of distant failure [20].…”
Section: Introductionmentioning
confidence: 99%